The role of smart packaging system in food supply chain - Chen, Shoue; Brahma, Sandrayee; Mackay, Jonathon; Cao, Changyong; Aliakbarian, Bahar (Journal of food science, 2020)
Food supply chain is a rapidly growing integrated sector and covers all the aspects from farm to fork, including manufacturing, packaging, distribution, storing, as well as further processing or cooking for consumption. Along this chain, smart packaging could impact the quality, safety, and sustainability of food. Packaging systems have evolved to be smarter with integration of emerging electronics and wireless communication and cloud data solutions. Although there are many factors causing the loss and waste issues for foods throughout the whole supply chain of food and there have been several articles showing the recent advances and breakthroughs in developing smart packaging systems, this review integrates these conceptual frameworks and technological applications and focuses on how innovative smart packaging solutions are beneficial to the overall quality and safety of food supply by enhancing product traceability and reducing the amount of food loss and waste. We start by introducing the concept of the management for the integrated food supply chain, which is critical in tactical and operational components that can enhance product traceability within the entire chain. Then we highlight the impact of smart packaging in reducing food loss and waste. We summarize the basic information of the common printing techniques for smart packaging system (sensor and indicator). Then, we discuss the potential challenges in the manufacturing and deployment of smart packaging systems, as well as their cost‐related drawbacks and further steps in food supply chain.